PELATIHAN KEORGANISASIAN MUHAMMADIYAH BAGI PENGURUS PCM DAN PCA DI KECAMATAN GEGERBITUNG DAN SUKARAJA - ojsnew (Universitas Muhammadiyah Sukabumi, 2015)
Muhammadiyah and 'Aisyiyah are similar Islamic organization, both as religious movement is static and as social stewardness movement is dynamics. Muhammadiyah statement is